Analisis Sastra Siber pada Puisi Api Drupadi Karya Retno Darsi Iswandari dalam Website basabasi.co Menggunakan Pendekatan Semiotik - Amelia Putri; Fita Puspitasari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The current development of digital technology has led to the emergence of new literary forms, one of which is cyber literature, utilizing the internet as a medium for the production and distribution of literary works. This phenomenon creates new dynamics in the literary world in terms of form, content, and interaction between readers and writers. This study aims to analyze the forms, characteristics, and implications of cyber literature as a literary expression that has developed in digital spaces. The method used in this analysis is descriptive qualitative with a literature review approach. Data were obtained through observations of cyber literary works found on various digital platforms, as well as through a review of relevant literature. The analysis results show that cyber literature has distinctive characteristics, such as interactivity, the use of multimedia, and openness to reader participation. In addition, the cyber poem "Api Drupadi" by Retno Darsi Iswandari includes hypertext and hyperlinks that connect the poem to other literary works and external websites. The conclusion of this analysis indicates that cyber literature is a form of literary evolution that not only adapts to technological advancement but also expands the traditional boundaries of literature through innovation and new media.